Social Mobility and Health Outcomes of UK Armed Forces Veterans: Insights from the ONS Longitudinal Study - Ibanez, Carles; Atherton, Iain; Ali, Umair (International Journal of Population Data Science, 2025)
Objectives This study aims to assess the impact of military service in the UK Armed Forces on social mobility and associated health outcomes. Additionally, it seeks to evaluate the effectiveness of imputing a variable to identify respondents who have served in the military. Methods The study utilizes data from the Office for National Statistics Longitudinal Study (ONS LS), which links a representative 1% sample of the population in England and Wales across multiple census waves. A matched analysis, employing a 3:1 ratio of service leavers to non-service leavers, will facilitate comparisons with the general population. Socio-economic status at age 16 or younger, as recorded in earlier census waves from 1971 onwards, will be compared with the most recent census enumeration to examine patterns of social mobility. The role of social mobility in explaining health disparities between service leavers and non-service leavers will be analyzed. Findings The demographic and socio-economic characteristics of the service leaver population in the ONS LS will be described, with a particular focus on their social circumstances and self-assessed health at the time of the 2021 census for England and Wales. Comparative figures will be presented to contrast the social circumstances of service leavers with those of the general population, both at the latest census and across previous census rounds. The extent to which current health disparities can be attributed to differences in childhood socio-economic status will be examined. Results will be reported for both descriptive analyses and matched comparisons, utilizing both original responses to the service leaver question and the imputed variable. Conclusion The findings will be discussed in relation to their implications for the future application of the service leaver data question in the census. Additionally, the study will consider the broader implications for policies aimed at supporting the health and well-being of the veteran community.